Lotman and the Baroque - Vidugirytė, Inga (Semiotika, 2022)
The title of this article refers to Gilles Deleuze’s work titled The Fold: Leibnitz and the Baroque and supposes a link, which could be established between the Baroque as a type of art, imagery, and a philosophical concept, as it was described by Deleuze, on the one hand, and the culture, its inner structure, and mechanisms (workings), as they were defined by Juri Lotman in his conception of the semiosphere, on the other. The article shows that the main concepts introduced by Leibniz and Deleuze find their counterparts in the semiotic space described by Lotman. Starting with the concept of a monad that both thinkers are concerned with, following conceptual pairs could be identified in their systems: a border – a fold, meaning-making – folding, semiosphere – total art, Deleuzian principle of cone – the hierarchy of monads in the semiosphere of Lotman. In the article, when placed side by side, both systems reveal their proximity as well as new aspects. The analysis leads to a conclusion that Lotman, who started his career as a strict structuralist, in the end, became a post-structural thinker revealing in his works the folded (Baroque) boundary between these two intellectual trends.